Corpus linguistics 25 years on: [Silver Jubilee of ICAME] - Facchinetti, Roberta (Language and computers, 2007)
Introduction; 1. Overviewing 25 years of corpus linguistic studies; Corpus linguistics 25+ years on; Corpus development 25 years on: from super-corpus to cyber-corpus; Seeing through multilingual corpora; Corpora and spoken discourse; 2. Descriptive studies in English syntax and semantics; An example of frequent English phraseology: distributions, structures and functions; The semantic properties of going to: distribution patterns infour subcorpora of the British National Corpus; The superlative in spoken English; Semantically-based queries with a joint BNC/WordNet database.